COMPARISON OF CARDIO-METABOLIC PARAMETERS BETWEEN THE DIFFERENT POLYCYSTIC OVARY SYNDROME PHENOTYPES AMONG FILIPINO WOMEN IN A TERTIARY HOSPITAL - Bisquera, Nichole Andrea; Dampil, Oliver Allan; Mendoza, Erick; Manalo-Mendoza , Yvette (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Polycystic Ovary Syndrome (PCOS) is the most common endocrinopathy in reproductive-aged women. It affects fertility and is also associated with significant metabolic disturbances. Women diagnosed with PCOS may have a heterogeneous presentation. The International Evidence-based Guidelines for the Assessment and Management of PCOS in 2018 stated that the presentation and manifestations of PCOS may have ethnic differences. Knowledge of the ethnic differences in the phenotypic clinical and metabolic profiles may assist clinicians in the diagnosis and management of PCOS in specific populations. METHODOLOGY This single-center, prospective cross-sectional study was done on 142 reproductive-aged women (18-45 years old) with PCOS as diagnosed by Rotterdam criteria. Participants were recruited from Endocrinology Obstetrics and Gynecology clinics. Demographic data, obstetric and gynecologic history, co-existing medical conditions, medication history, vital signs, and anthropometric measurements were collected. The presence of clinical signs of hyperandrogenism was evaluated (hirsutism with mFG scores, acne, and alopecia). Results of 75-gram OGTT/FBS, lipid profile, fasting insulin, complete blood count, and transvaginal/transrectal ultrasound were collected. BMI, HOMA-IR, TG/HDL ratio, and Neutrophillymphocyte ratio (NLR) were computed. To determine the differences in mean, median, and frequency between phenotype groups, One-way ANOVA, Kruskal-Wallis test, and Fisher’s Exact test were used, respectively. RESULTS A total of 142 participants were included in the analysis. Overall, the mean age was 30.57 years. The highest proportion among the study participants was phenotype A (37.32%). Clinical signs of hyperandrogenemia were highest in the hyperandrogenic phenotypes (A,B) (p = 0.05). Insulin resistance similarly was also comparable across phenotypes, however, Phenotype A had the highest fasting insulin level (median 17, p = 0.047), and HOMA-IR values (median 4.70, p = 0.048). Phenotype A had the highest weight, and BMI across groups (median 82 kg, median 31.69 kg/m2, p = 0.023, and p = 0.032, respectively). Markers of central adiposity (waist circumference and waist-to-hip ratio) were highest in Phenotype A, but were also elevated in the oligo-anovulatory phenotypes B and D (p = 0.005). Participants in phenotype D had significantly higher TG/HDL ratios. NLR scores were similar across all phenotypic groups (median 2, p = 0.40). CONCLUSION In conclusion, this study provides a comprehensive metabolic and phenotypic profile in a clinical population of adult reproductive-age Filipino women with PCOS. The most common phenotype is the classic/hyperandrogenic type, but a greater proportion of non-hyperandrogenic phenotypes in this population suggests a greater role of the presence of PCO morphology in the diagnosis. There is a high prevalence of obesity and central adiposity in Filipinos with PCOS. The oligo-anovulatory phenotypes (A, B, and D) present with greater metabolic dysfunction. Markers for adiposity and determination of insulin resistance should be included in the assessment of PCOS patients because these measures inform risk for development of co-morbidities, allow secondary prevention and help clinicians tailor long-term management of patients with PCOS.